2010
DOI: 10.1007/s10096-010-1020-1
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and characteristics of ertapenem-nonsusceptible Escherichia coli in a Taiwanese university hospital, 1999 to 2007

Abstract: The present study was conducted to investigate the prevalence and characteristics of ertapenem-nonsusceptible (ETP-NS) Escherichia coli in a Taiwanese university. A total of 9,722 isolates collected in 1999, 2003, 2005, and 2007 were examined. Overall, 1.0% of all isolates from 66 patients were interpreted as ETP-NS on the basis of the disk diffusion test result. Most of these isolates were clonally unrelated and showed low-level ertapenem resistance, the production of CMY-2 cephalosporinase (86.4%), and decre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 21 publications
2
14
1
Order By: Relevance
“…Unlike OmpA, the variation in OmpC may be much higher than we thought. Our previous data showed a higher mutation rate of the ompC gene (truncated forms or insertion) in multidrug-resistant E. coli (23,41). We also found that the OmpC mutant can be detected from natural selection, and these mutants not only had similar carbapenems and cefepime resistance, but also had similar serum bactericidal activities ( Fig.…”
Section: Discussionsupporting
confidence: 66%
“…Unlike OmpA, the variation in OmpC may be much higher than we thought. Our previous data showed a higher mutation rate of the ompC gene (truncated forms or insertion) in multidrug-resistant E. coli (23,41). We also found that the OmpC mutant can be detected from natural selection, and these mutants not only had similar carbapenems and cefepime resistance, but also had similar serum bactericidal activities ( Fig.…”
Section: Discussionsupporting
confidence: 66%
“…It remains undefined if there is any difference in long-term outcome between different treatment groups. Finally, in Taiwan there are no indigenous isolates with KPC or NDM enzymes, and the mechanisms mediating carbapenem resistance in E. coli isolates were production of AmpC beta-lactamases in conjunction with porin deficiency (2,25). The correlation between clinical outcome and carbapenem susceptibility may not be generalized to Western countries with a variable prevalence of KPC or NDM beta-lactamases among Enterobacteriaceae isolates.…”
Section: Discussionmentioning
confidence: 99%
“…Cell debris was removed by centrifugation, and 2 l of supernatant was used as a source of template DNA in a 50-l PCR. Strains were analyzed for ␤-lactamase genes (bla CTX-M , bla OXA , bla SHV , and bla TEM ), using the primers described previously (27,28). The purified PCR products were directly sequenced using the automated ABI Prism 3730 DNA sequencer (Applied Biosystems, Foster City, CA).…”
Section: Methodsmentioning
confidence: 99%